Implementing Blockchain-Enhanced Version Control Systems To Optimize Software Development Life Cycles (International Journal of Scientific Research and Management (IJSRM), 2022)
This research addresses the integration of blockchain technology to improve the software development life cycle (SDLC) through version control systems (VCS). However, managing code versions and supporting other developers in software development isn’t just enough with the traditional VCS, for example, Git. It, however, lacks the inherent security, transparency, and automation required for modern distributed software projects. The limitations of current tax systems can be overcome with the help of blockchain technology — it is a decentralized, immutable, transparent technology. Based on the blockchain, the system becomes more secure, transparent, and more efficient. Among the most important benefits are enhanced security against unauthorized changes, traceable code changes tracing, improved collaboration, and code reviews, testing, and deployment automated with smart contracts. While having advantages the blockchain-enhanced version control system (BEVCS) has challenges like scalability, integration complexity, and cost of implementation. This paper ends with some recommendations of how further research can be done and what can be practical stuff to implement. Integration of blockchain in VCS offers transformative possibilities to improve the efficiency and security in VCS, however these challenges need to be overcome to reveal the full potential of blockchain.